Optimalisasi Keterampilan Desain Media Belajar Interaktif Berbasis Digital Bagi Guru-Guru di Malaka untuk Meningkatkan Kualitas Pembelajaran - Dorthea Maria Woga Nay; Heru Christianto; Arvinda C. Lalang; Eka C. G. Kerihi (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Technological advances provide educators with the freedom to create quality learning that meets the needs and learning environment of students. A crucial aspect for teachers to consider in realizing effective learning is the use of interactive learning media tailored to the characteristics and needs of students. The use of digital technology to develop interactive learning media is a necessity in today's learning process. Training and mentoring for teachers in Malaka to develop interactive and innovative digital media is based on the need to improve their competency and skills in utilizing technology to develop learning media. This activity aims to improve teachers' competency and skills in utilizing technology to design engaging and interactive digital-based learning using Book Creator and QuizWhizzer. Monotonous learning activities, often based on lectures and group discussions, with the use of conventional learning media, tend to make students passive and easily bored, resulting in a lack of student interest in learning and a decline in the quality and outcomes of learning. Furthermore, technological developments demand increased competency, including in preparing engaging learning media. Therefore, through this training activity, teachers are provided with guidance and training in developing interactive learning media so that the resulting products can be directly used in the learning process. The developed media is designed to be interactive and engaging, thereby increasing student motivation. Furthermore, this activity also encourages teachers to be more creative and innovative in creating learning media that can attract student interest. The training activities ran smoothly and effectively, as evidenced by the high enthusiasm of teachers and the increase in knowledge and skills related to the training material. The mentoring results also showed an improvement in the quality of learning through active student interaction in learning with the help of digital learning media, which resulted in improved interest and learning outcomes.